Human Regulatory Dendritic Cells Develop From Monocytes in Response to Signals From Regulatory and Helper T Cells - Zhang, Xiangyue; Zheng, Pingping; Prestwood, Tyler R.; Zhang, Hong; Carmi, Yaron; Tolentino, Lorna L.; Wu, Nancy; Choi, Okmi; Winer, Daniel A.; Strober, Samuel; Kang, Eun-Suk; Alonso, Michael N.; et al. (Frontiers in Immunology, 2020)
Dendritic cells (DCs) are powerful antigen presenting cells, derived from bone marrow progenitors (cDCs) and monocytes (moDCs), that can shape the immune response by priming either proinflammatory or tolerogenic immune effector cells. The cellular mechanisms responsible for the generation of DCs that will prime a proinflammatory or tolerogenic response are poorly understood. Here we describe a novel mechanism by which tolerogenic DCs are formed from monocytes. When human monocytes were cultured with CD4+FoxP3+ natural regulatory T cells (Tregs) and T helper cells (Th) from healthy donor blood, they differentiated into regulatory DCs (DCReg), capable of generating induced Tregs from naïve T cells. DCReg exhibited morphology, surface phenotype, cytokine secretion, and transcriptome that were distinct from other moDCs including those derived from monocytes cultured with Th or with GM-CSF/IL-4, as well as macrophages (Mo). Direct cell contact between monocytes, Tregs and Th, along with Treg-derived CTLA-4, IL-10 and TGF-beta, was required for the phenotypic differentiation of DCReg, although only IL-10 was required for imprinting the Treg-inducing capacity of DCReg. High ratios of Treg:Th, along with monocytes and DCReg similar in function and phenotype to those induced in vitro, were present in situ in human colorectal cancer specimens. Thus, through the combined actions of Tregs and Th, monocytes differentiate into DCs with regulatory properties, forming a positive feedback loop to reinforce Treg initiated immune regulation. This mechanism may contribute to immune tolerance in tissues such as tumors, which contain an abundance of Tregs, Th and monocytes.